Perancangan dan Pengujian Pompa Hidram - Salimin; La Ode Ahmad Barata (Piston: Jurnal Teknologi, 2021)
One technology that can be used to move water from a low place to a high place is a water pump without the use of electricity and fuel (Hydraulyc Ram/Hydraulic Pump). A water pump without the use of electricity and fuel (Hydraulyc Ram/Hydram Pump) is an automatic pumping device that uses water to lift some of the water flow to a higher place. The energy source for water pumps without the use of electricity and fuel (Hydraulyc Ram / Hydram Pumps) comes from high pressure which is caused by the phenomenon of water blowing due to a sudden change in speed of the water flow by closing the valve, so this pump does not require an external energy supply such as fuel oil or electricity. This article presents a report on the design, manufacture and performance field testing of hydraulic pumps. The test results show that the pump design can drain 0.3 liters/second of water with a maximum head of 8.1 meters and a distance of 10.5 meters. By looking at the potential for its use which is quite broad, research to optimize this pump needs to be continuously carried out in order to obtain a design that is quite accurate in accordance with field conditions in Indonesia.